Neglected left intraparotid facial nerve schwannoma causing complete facial nerve palsy: A case report (Bangladesh Journal of Medical Science, 2018)
Extracranial schwannomas in the head and neck region are relatively rare neoplasms. The tumours are slow growing and often unnoticeable. The nerve of origin is unable to be determined until the time of surgery. Proper preoperative assessment of the disease can be done by imaging studies such as magnetic resonance imaging. The treatment for these tumours is surgical resection with preservation of the neural pathway. We report a case of left intraparotid facial nerve schwannoma in a middle-aged lady causing complete facial nerve paralysis. The clinical features, diagnostic possibilities and management are discussedBangladesh Journal of Medical Science Vol.17(4) 2018 p.680-682